Evaluation of Employment Benefits of Ultra-Heavy Trucks: Wisconsin Case Study - (:unkn) unknown (My University, 2014)
Allowing very heavy trucks, without permits, on United States' highways has been a subject of discussion in the past, and many politicians and industry advocates have argued that there are some benefits to much heavier trucks. Benefits include better air quality, reduced fuel usage, and increased industrial efficiency. The economic analysis of heavier trucks, however, remains incomplete. One way to measure economic benefits is by assessing employment growth. Wisconsin is used as a case study to evaluate employment benefits of ultra-heavy trucks. The current regulation of the maximum gross vehicle weight on all axles in Wisconsin is 80,000 pounds. Three scenarios of ultra-heavy trucks are proposed to have a much greater weight limitation - 100,000 pounds, 120,000, and 140,000 pounds. The thesis focuses on four analyses that evaluate employment growth due to cost savings, accessibility, mode shift, and industry restructuring. The cost savings are calculated by using the CFIRE Truck Cost Model. The cost saving is also used to estimate the job loss in trucking industry. The effects of accessibility improvements are estimated by using Montana HEAT business attraction model, previously adapted for Wisconsin. The mode shift analysis applies the cross elasticity between rail and truck to quantify the diversion from rail to truck. The numbers of employment associated with diversion from rail is estimated. IMPLAN model and REMI model, economic analysis tools, are implemented to understand the impacts of ultra-heavy trucks towards other industries. IMPLAN model is a basic input-output economic model uses the Social Accounting Matrix and multipliers model. REMI model is a dynamic model that integrates an econometric model, an input-output model, a general equilibrium model, and economic geography methodologies. Overall, implementing ultra-heavy trucks will create more jobs in both trucking industries and other industries. It also improves the efficiency of trucking industry that makes it more competitive than other modes, which enhance the growth within trucking industry. In the long run, trucking industries will expand growth of the whole economy through exports and more economic activities. From this analysis, the critical weight of ultra-heavy trucks is inconclusive as this study only evaluates employment impacts. Other considerations in safety, pavement, bridges, environment, and others are needed before implementing ultra-heavy trucks.
Keywords: Economic Impact Analysis; Employment; Transportation Analysis; Truck Cost; Truck Weight; Ultra-Heavy Trucks